2003
DOI: 10.1590/s0102-05362003000400021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different oxygen, carbon dioxide and nitrogen combinations employed to extend the shelf life of fresh-cut collard greens

Abstract: A lthough commercialized at higher prices when compared to fresh products, fresh-cut fruits and vegetables have the advantage of being perceived by customers to be fresher than other products, such as frozen or canned food. Since 1994, "fresh" has remained the most desirable food label claim for 79% of american customers, followed by low fat (62%), and natural MORETTI, C.L.; ARAÚJO, A.L.; MATTOS, L.M. Evaluation of different oxygen, carbon dioxide and nitrogen combinations employed to extend the shelf life of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 12 publications
4
13
1
3
Order By: Relevance
“…Under these conditions, the decrease in chlorophyll content was largely influenced by higher levels of in-pack O 2 alone. These results were in agreement with the earlier reported observations of Moretti et al, (2003) where an initial decrease in the chlorophyll content was observed for green collards under the influence of high or ambient levels of O 2 . As the storage period progressed and a steady state was attained, CO 2 build-up took place inside the film packages leading to stabilization in the chlorophyll retention levels in both types of film packages.…”
Section: Effect Of Map On Pigmentssupporting
confidence: 94%
“…Under these conditions, the decrease in chlorophyll content was largely influenced by higher levels of in-pack O 2 alone. These results were in agreement with the earlier reported observations of Moretti et al, (2003) where an initial decrease in the chlorophyll content was observed for green collards under the influence of high or ambient levels of O 2 . As the storage period progressed and a steady state was attained, CO 2 build-up took place inside the film packages leading to stabilization in the chlorophyll retention levels in both types of film packages.…”
Section: Effect Of Map On Pigmentssupporting
confidence: 94%
“…Use of low O 2 (1-5 %) and high CO 2 (5-10 %) concentrations, in combination with storage at low temperatures maintains sensorial as well as microbial Partial pressure of oxygen , kPa Respiration rate, ml/kg-h c) Temperature: 20 o C Fig. 3 Graphical representation of variability in inhibition of oxygen consumption rate of whole and end cut baby corn by carbon dioxide with increase in temperature quality of fresh-cut vegetables (Fonseca et al 2002;Moretti et al 2003). These conditions inhibit enzymatic browning reaction on the cut surfaces and the structure of plant tissue sustains its typical turgoricidy and crispness for a longer period.…”
Section: Resultsmentioning
confidence: 99%
“…Use of low O 2 (1-5 %) and high CO 2 (5-10 %) concentrations, in combination with low temperature storage maintains sensorial quality and extends the shelf life of fresh-cut vegetables (Fonseca et al 2002;Moretti et al 2003). Discolouration of cut surfaces due to enzymatic browning, yellowing of green vegetables, and pale colour of bright vegetables are the main defects of fresh-cut produce (Nobile et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Use of low O 2 (1–5%) and high CO 2 (5–10%) concentrations, in combination with storage at low temperatures, maintains sensorial as well as microbial quality of fresh‐cut vegetables (Geeson 1989, Fonseca et al. 2002 and Moretti et al. 2003).…”
Section: Introductionmentioning
confidence: 99%